Neoadjuvant chemotherapy enriches for drug-tolerant persisters in PDAC - Bailey, Peter; Neoptolemos, John P. (Nature cancer, 2023)
Resected pancreatic cancer treated pre-operatively with chemotherapy is enriched for cells that co-express GATA6, KRT17 and CYP3A. Persistent expression of GATA6hi and KRT17hi is associated with poor survival after treatment with mFOLFIRINOX, but not gemcitabine. CYP3A-expressing drug detoxification pathways metabolize the prodrug irinotecan, a constituent of mFOLFIRINOX, leading to persistent drug tolerance.
Gesehen am 16.10.2023